Mature Myotubes Generated From Human-Induced Pluripotent Stem Cells Without Forced Gene Expression - Fujiwara, Kei; Yamamoto, Risa; Kubota, Tomoya; Tazumi, Atsutoshi; Sabuta, Tomoka; Takahashi, Masanori P.; Sakurai, Hidetoshi (Frontiers in Cell and Developmental Biology, 2022)
Human-induced pluripotent stem cells (hiPSCs) are a promising tool for disease modeling and drug screening. To apply them to skeletal muscle disorders, it is necessary to establish mature myotubes because the onset of many skeletal muscle disorders is after birth. However, to make mature myotubes, the forced expression of specific genes should be avoided, as otherwise dysregulation of the intracellular networks may occur. Here, we achieved this goal by purifying hiPSC-derived muscle stem cells (iMuSC) by Pax7-fluorescence monitoring and antibody sorting. The resulting myotubes displayed spontaneous self-contraction, aligned sarcomeres, and a triad structure. Notably, the phenotype of sodium channels was changed to the mature type in the course of the differentiation, and a characteristic current pattern was observed. Moreover, the protocol resulted in highly efficient differentiation and high homogeneity and is applicable to drug screening.